Analisis Pengaruh Harga, Kualitas Produk, dan Tren Terhadap Keputusan Pembelian Thrifting Pada Generasi Z di Kalangan Mahasiswa Universitas HKBP Nommensen Medan - Simanjorang, Lasmina Kajol; Manalu, Darma; Tobing, Artha Lumban (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This study aims to determine the effect of price, product quality, and trends on thrifting purchasing decisions on Generation Z among HKBP Nommensen University Students Medan. This study was conducted using a quantitative method. Data collection techniques using questionnaires. Based on hypothesis testing with the t test, the t-count value for the price variable was 2.530 where the value was > from t table 1.986 and the significant value for the price variable was 0.013 <0.05 (5%). For the product quality variable, the t-count value was 0.960 where the value was <from t table 1.986 and the significant value for the product quality variable was 0.340 >0.05 (5%). For the trend variable, the t-count value was 5.874 where the value was >1.986 and the significant value for the trend variable was 0.000 <0.05 (5%). So it can be concluded, price and trend have a positive and significant effect on thrifting purchasing decisions among Generation Z among HKBP Nommensen University Students. While product quality does not have a positive and insignificant effect on thrifting purchasing decisions among Generation Z among HKBP Nommensen University Students Medan. And the f test obtained an f count value of 20.300 where this value is > from f table of 3.09. Along with a significant value of 0.000 < from a significance level of 0.05. So it can be concluded that simultaneously price, product quality and trends together have a positive and significant effect on thrifting purchasing decisions among Generation Z.